Implementasi Starategi POAC (Planning, Organizing, Actualiting, Controlling) dalam Perencanaan Karir dan Akademik Siswa SMK Sasmita Jaya 2 - Restu Cahaya Aini; Azmy Azizah; Diva Alisya Putri; Mariam Nur Azizah Fitriani; Lilis Setyawati; Sri Utaminingsih; Ruknan Ruknan; Nuryati Djihadah (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Vocational High School (SMK) students' lack of preparation for their future often contributes to the high unemployment rate among vocational graduates. This Community Service (PKM) activity aims to implement the POAC (Planning, Organizing, Implementing, and Controlling) management function as a framework for SMK Sasmita Jaya 2 students to manage their career and academic planning more systematically and purposefully. The methods used include outreach, participatory discussions, and mentoring in utilizing professional digital platforms to support job readiness and self-development. The activity results indicate an increase in student awareness in setting clearer, more realistic, and measurable post-graduation goals. The implementation of the POAC strategy has been proven to help students transform intentions into concrete steps through the development of a focused and sustainable action plan. In addition, students are able to develop a more structured career roadmap based on their interests and competencies, and increase their confidence in facing job selection and further education. This program also encourages collaboration with industry and alumni to broaden students' horizons and future career opportunities.